Impact of molecular subtypes classification concordance between preoperative core needle biopsy and surgical specimen on early breast cancer management: Single-institution experience and review of published literature. Issue 4 (April 2017) - Meattini, I.; Bicchierai, G.; Saieva, C.; De Benedetto, D.; Desideri, I.; Becherini, C.; Abdulcadir, D.; Vanzi, E.; Boeri, C.; Gabbrielli, S.; Lucci, F.; Sanchez, L.; et al.
Abstract: Background: Core needle biopsy (CNB) plays a crucial role as diagnostic tool for breast cancer (BC). The characterization of biomarkers status before surgical treatment is crucial when primary systemic therapy is a therapeutic option. The aim of this analysis was to report concordance between preoperative CNB and surgical specimen (SS) in evaluating biomarkers and molecular subtypes. Methods: Data have been collected from a cohort of 101 patients affected by early BC treated at Careggi Florence University Hospital, between January 2014 and March 2015. The conformity between molecular subtype classification was tested using kappa (κ) test. Results: Mean age was 57.5 years (range 29–86). There was concordance between the estrogen receptor (ER) assessment on CNB and SS in 95 cases (94.1%). Concordance of the progesterone receptor (PgR) assessment was observed in 89 cases (88.1%). Concordance for detecting immunohistochemistry-assessed BC molecular subtypes was 87.1% (κ = 0.78). Concerning Ki-67 evaluation, we report a concordance rate of 88.1% (κ = 0.68). The evaluation of luminal A plus luminal B/HER negative subgroup showed a κ-value of 0.65. Conclusions: CNB showed good accuracy in evaluating hormonal receptors status, HER2, and BC molecular subtypes. Evaluation of Ki67 status was less accurate than other biomarkers; therefore, we recommend that it should be detected both on CNB and SS samples, especially in hormonal positive HER2 negative tumors, in order to avoid a misclassification of tumor subtypes that could lead to an omission of potential effective systemic therapy.